Terrible triad elbow with tricep avulsion: diagnostic challenge and treatment dilemma: case report - Katariya, Jeetendra Prakash; Khatri, Anup Milind; Kumar, Ashish (International Journal of Research in Orthopaedics, 2021)
Triceps Avulsion with terrible triad of elbow is a rare presentation and often missed at the time of presentation. The aim of this case report is to identify triceps avulsion in patients with terrible triad elbow and help in its management and post-operative mobilization protocol. We report a case of 40-year male, a case of road traffic accident with right elbow terrible triad injury with triceps avulsion. The radial head was fixed with 2.5 mm locking plate and screws and suture anchor was used for triceps avulsion. Elbow mobilization was started at 2 weeks post-operatively. In patients with terrible triad injuries, diagnosis of triceps avulsion is very challenging because of swelling, pain and difficult to examine triceps for extension power. It is important to know this type of presentation of triceps avulsion with terrible triad to address the diagnostic pathway in the right direction and to treat them promptly. Missing triceps avulsion in complex injuries may hamper post-operative elbow range of movements in form of extension lag or triceps weakness.